Deformations in translating modern Ukrainian war fiction into English – A psycholinguistic study of "Інтернат"/The Orphanage by Serhiy Zhadan - Kalishchuk, Diana; Zasiekin, Serhii (Lesya Ukrainka Eastern European National University, 2024)
The article is focused on analysing linguistic deformations in translating modern Ukrainian war fiction into English. The research material is the novel "Інтернат"/ The Orphanage by Serhiy Zhadan and its translation into English. Translation deformations, or "deforming tendencies" (Berman, 2000), are viewed as systemic psycholinguistic distortions, arbitrary and non-arbitrary, of formal and content source text characteristics. Three main groups of translation deformations have been identified in the text under analysis – lexical, stylistic, and grammatical. Lexical deformations include calque translation, concretisation and modulation. Due to their low frequency, they are not viewed as typical. Stylistic deformations fall into synonymous substitution, logisation, explication, expressivation, modernisation, antonymous translation, and compensation. Synonymous substitution and logisation are the most frequent types; therefore, they may be considered prototypical. They are mainly concerned with reproducing characters’ names and descriptions, names or descriptions of military and civil vehicles and tools, colloquial expressions and 'surzhyk'. Grammatical deformations constitute the most significant group. They comprise substitutions and permutations of different types, deletion of words/phrases/sentences, addition of words/phrases, and changes in punctuation. The style of Serhiy Zhadan is characterised by specific syntactical-stylistic features, such as the tendency to use extremely long sentences, high frequency of repetitions of different types, and specific punctuation. Therefore, deleting repetitions, intensifiers, discourse markers, and even sentences is the most recurrent type of grammatical deformation, followed by substitution–division of sentences, which may be treated as prototypical grammatical deformations in the analysed text. The results of the psycholinguistic analysis show the availability of normalisation, implicitation, emotional amplification, levelling-out, and simplification in the target version of the novel.
Keywords: war fiction; translation deformations; Serhiy Zhadan; The Orphanage; Ukrainian; English; LIWC; psycholinguistics